Strategic Management of the Balanced Scorecard and Blue Ocean in Elementary Education Institutions - Anwar, Kasypul (JURNAL AL-TANZIM, 2022)
This study aims to understand how the implementation of the balanced scorecard and blue ocean in primary education institutions in the city of Banjarmasin. This research uses a case study qualitative approach, where interviews, observations, and documentation are used as media to obtain valid and accountable data. The data analysis follows an interactive analysis model, which collects, reduces, and presents data to conclude. The results showed that the implementation of the balanced scorecard and blue ocean in primary education in Banjarmasin City could be grouped into 4, namely: first, school management; second, community participation; third, teaching and learning activities; and fourth output. The non-implementation of the balanced scorecard and blue ocean policies is caused because the parties involved in their implementation do not want to cooperate, work half-heartedly, or do not fully master the problem so that no matter how persistent their efforts are, they cannot overcome the existing obstacles.